Stimulating Repeat Purchase Behavior Case Study of Solosso Company - Klimo, Ján; Karlíček, Miroslav, 1979-; Novotný, Ota, 1971-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The goal of this thesis is to propose strategies that profitably stimulate repeat purchase behaviour of Solosso's customers, Solosso being an e-commerce start-up producing custom made dress shirts. In order to accomplish the stated goal, research has been conducted into the existing body of literature about the subject, models for managing customers for value have been presented and applied on Solosso's customer database. Additionally, customer survey has been conducted to better understand customers' behaviour. Based on the applied models and the findings from the survey, the thesis delivers a set of recommendations on how to improve the product, what customers to acquire and, finally, what strategies to employ in order to profitably stimulate repeat purchase behaviour of the four main groups of Solosso's customers. The methods and strategies are expected to generate substantial incremental profits and may be implemented in other businesses as well.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses